The The Role and Challenges of Gampong Customary Courts in Resolving Customary Criminal Cases in Lhokseumawe City - Muhammad Rudi Syahputra; Herlin; Zulfiyanda; Riska (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The Aceh customary courts play a pivotal role in resolving societal conflicts, particularly those not addressed by the formal justice system. The formal system often remains inaccessible due to remote locations, high costs, and the complexities of judicial administration, posing significant challenges for communities, especially in Kota Lhokseumawe. This study examines two key issues: the authority of gampong customary courts in addressing customary criminal cases and the resolution models employed by these courts to reduce such cases in Kota Lhokseumawe. Using a descriptive qualitative method based on field research with a normative-empirical juridical approach, this study reveals that the authority of gampong customary courts represents a form of local wisdom that remains highly relevant in Indonesia, particularly in regions with strong customary traditions like Kota Lhokseumawe. This authority is confined to 18 types of cases as stipulated in Article 13 of Aceh Qanun No. 9 of 2008 on the Development of Customary Life and Customs and Aceh Governor Regulation No. 60 of 2013 on the Settlement of Customary Disputes. Through deliberation (musyawarah) and consensus (mufakat), these courts effectively restore social harmony and resolve conflicts peacefully. However, challenges such as the formalization and documentation of customary decisions, training for customary leaders in formal legal procedures, and the inconsistent application of customary law persist. Addressing these challenges is essential to ensure that customary courts continue to contribute to maintaining social order and justice at the local level.